Changes in circadian dynamics of animals in response to noise (Experimental biology, 2018)
In this paperare considered the changes in circadian dynamics in animals under the influence of stress factors.One of the reasons of such an interest in chronobiological research lays in data gathering, that unquestionably provides evidence of relation between organism’s circadian rhythms and arousal of various pathogenic conditions in humans. Noise is a stress-factor. Development of such a condition causes tension of hypothalamus-pineal body-corticoadrenal system. Corticosteroid hormones, cholesterol and glucose concentrations in blood increase and eosinophils concentration falls. Due to these disorders, changes in circadian rhythms of the organism arise. Nevertheless, using such methods in chronomedicine, as amplitude changes in rhythms, change of mesor or period of rhythm independently is sufficiently acceptable and justified in a number of specific cases. Amplitude increase (decrease) of circadian rhythm under influence of stress. The amplitude of circadian rhythms possesses exclusively important significance for assessment of functional state of a human.Key words:circadian rhythm, noise, circadian dynamics, desynchronosis, chronomedicine.